PERBEDAAN KECERDASAN EMOSIONAL DILIHAT DARI PILIHAN SESEORANG SAAT BERHADAPAN DENGAN DILEMA MORAL AGAMA - Lutfiyah Hani; Subhan El Hafiz (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
Aim of this research to see difference of emotional intelligence from one's choice when faces dilemmas situation of religious value. This research using quantitative approach method and subject of this study for respondents aged 17-50 years and Muslim as many as 153 respondents. The measurement instruments are the emotional intelligence scale, “trait meta-mood scale” (TMMS) and dilemmas situation instrument. Data analyzed by compare mean t-test independent sample. The results shows no difference of emotional intelligence seen from individual reasons to decide their choices, namely emotional and rational (MD=0.710; p>0.05). But when the data analyzed based on groups choice the results shows significant difference in emotional intelligence seen from group which choose not to do plural prayer (jama’), which is higher emotional intelligent in a group who choose with rasional reason than emotional (MD=0.047; p<0.05). Hypoteses also rejected in group which choose rukhsoh (MD=0.313; p>0.05). This resuls shows emotional intelligent can affecting the reason one to choose but limited to certain type of choosen.